Near-infrared light sensitive liposomes for the enhanced photothermal tumor treatment by the combination with chemotherapy - You, Jian (2014)
PURPOSE: To develop a near-infrared (NIR) light-sensitive liposome, which contains hollow gold nanospheres (HAuNS) and doxorubicin (DOX), and evaluate their potential utility for enhancing antitumor activity and controlling drug release. METHODS: The liposomes (DOX&HAuNS-TSL) were designed based on a thermal sensitive liposome (TSL) formulation, and hydrophobically modified HAuNS were attached onto the membrane of the liposomes. The behavior of DOX release from the liposomes was investigated by the dialysis, diffusion in agarose gel and cellular uptake of the drug. The biodistribution of DOX&HAuNS-TSL was assessed by i.v. injection in tumor-bearing nude mice. Antitumor efficacy was evaluated both histologically using excised tissue and intuitively by measuring the tumor size and weight. RESULTS: Rapid and repetitive DOX release from the liposomes (DOX&HAuNS-TSL), could be readily achieved upon NIR laser irradiation. The treatment of tumor cells with DOX&HAuNS-TSL followed by NIR laser irradiation showed significantly greater cytotoxicity than the treatment with DOX&HAuNS-TSL alone, DOX-TSL alone (chemotherapy alone) and HAuNS-TSL plus NIR laser irradiation (Photothermal ablation, PTA, alone). In vivo antitumor study indicated that the combination of simultaneous photothermal and chemotherapeutic effect mediated by DOX&HAuNS-TSL plus NIR laser presented a significantly higher antitumor efficacy than the PTA alone mediated by HAuNS-TSL plus NIR laser irradiation. CONCLUSIONS: Our study could be as the valuable reference and direction for the clinical application of PTA in tumor therapy.